Le faux miroir de l’objectif : enquête sur la fabrication des données spatiales - Marvin Freyne (L'Espace Politique)
The following article deals with the production of spatial data by using drones and satellites with a particular emphasis on the civil and humanitarian sphere. Though different spaces are explored, the investigation mainly focuses on the Syrian territory which gathers a wide range of actors that experiment many technical means. This research falls within a multidisciplinary perspective related to social studies and particularly builds upon geographical and anthropological contribution works. The investigation was carried out between Summer 2019 and October 2021. In order to achieve successful research completion, the investigation relies on thorough study of literature works related to drones and satellites on military and humanitarian field. This is part of a Post-Tomnod context where participatory projects are flourishing. Two books were particularly inspiring to this end: La souffrance à distance (1993) by Luc Boltanski and Théorie du drone (2013) by Grégoire Chamayou. Moreover, a number of qualitative interviews were conducted with individuals whose diverse profiles are representative of the many different actors that belong to the space-based data field. Each of them intervenes in the humanitarian, military and engineering field as well as in spatial agencies. So as to contribute to the research on spatial data through an anthropological investigation on the development of the related tools, we shall explain the process of data fabrication with a look at the history, the use and the different representations of the world. Then, the idea is to present an overview of data use so as to analyze the political space especially in terms of information, surveillance, risks and crisis prevention. Thus, beyond its use as a power tool, space-based data can be seen as a tool for critical examination and to control power. Indeed, these tools can be used by humanitarian workers to monitor population shifts following an unexpected bombing.Nonetheless, these interests must be balanced due to certain backlashes. In this criticism of the criticism itself, we shall mention “God’s eye” point of view which is allowed by these tools that necessarily provide a panoptic gaze upon the people who are to be observed. The issue that this panoptic gaze comes along with is that it reifies observed individuals. This implies other difficulties. One of which is linked to the reality effect provoked by these images. This effect can be misleading because it deals with subjective realities as a result of their environment and analysis. God’s eye ends up being fooled by a sham. Finally, it is crucial to put the technological imperative back into its political context and into the standards it meets. Indeed, by dint of not questioning the challenges linked to the reasons why a crisis occurred but rather on the means that can be used to help the victims, the process can be alienating and can induce a latent depolitization of crises. Eventually, the use of spatial-based data brings a lot of benefits especially in terms of information, surveillance, prevention, and critical analysis of power. However, these assets must be questioned. Drones have become fearsome power tools as well as opposition tools. Both drones and satellites purpose constitute a false mirror of reality to the extent that, due to the manufacturing of spatial-based data, they reveal subjective realities.